Compliance Evaluation of The GMP and SSOP Implementation of Frozen Tuna Loin Processing in PT. XYZ, Bitung - Hariyoto, Fitroh Dwi; Ticoalu, Fidel; Yudana, IGP Gede Rumayasa; Maringka, Gabriela Stela (PELAGICUS, 2024)
The implementation of basic feasibility programs such as Good Manufacturing Practices (GMP) and Sanitation Standard Operating Procedures (SSOP) must be carried out properly to maintain and ensure the feasibility and food safety of processed fishery products in the fisheries industry sector as one of the main components of the Indonesian economy. Bitung City as the center of fisheries industry in Indonesia has a variety of Fish Processing Units (UPI) that produce various processed products, such as frozen tuna loin as a primer commodity. This research, which was conducted from February to May 2023 through direct observation of the implementation of GMP and SSOP, aims to assess the suitability of GMP and SSOP implementation in the frozen tuna loin production process. Qualitative, quantitative, and descriptive comparative analysis were conducted based on the Regulation number 75/M-IND/PER/7/2010 from the Minister of Industry for the analysis of GMP implementation and the Regulation number PER.19/MEN/2010 from the Minister of Marine and Fisheries Affairs on SSOP conformity. The results obtained during the study showed that the percentage of GMP implementation conformity was 83% of the 200 items assessed. Meanwhile, of the 28 SSOP items that have been applied to frozen tuna loin processing, the suitability of the application reached 78.57% and is running well, although there are some minor errors. Compliance evaluation needs to be carried out in the form of improvements to 34 non-conformities in GMP and 6 improvements in SSOP implementation to improve the safety of frozen tuna loin products.